The role of agricultural development projects in poverty reduction in the OR Tambo District Municipality of the Eastern Cape Province South Africa - Terblanche, S.E. (Stephanus Esaias), 1940- (University of Pretoria, 2019)
Dissertation (MSc (Agric))--University of Pretoria, 2018.